Effect of nitrogen, phosphorus and sulphur on growth, yield and quality of Indian mustard [Brassica juncea (L.) Czern and Coss.]: EFFECT OF NITROGEN, PHOSPHORUS AND SULPHUR ON GROWTH, YIELD AND QUALITY OF MUSTARD - ZALAK Y CHAUHAN; D K PATEL; C K PATEL (Journal of Oilseeds Research, 2021)
A field experiment was carried out at Agronomy Instructional Farm, Chimanbhai Patel College of Agriculture, Sardarkrushinagar DantiwadaAgriculturalUniversity,Sardarkrushinagar, Gujarat during the winter 2018-19 to study the effect of different nutrient levels on growth, yield and quality of Indian mustard. Twelve treatment combinations viz., three levels of nitrogen (50, 75 and 100 kg N/ha), two levels of phosphorus (50 and 75 kg P2O5/ha) and two levels of sulphur (40 and 60 kg S/ha) were evaluated as per randomized block design in three replications. Soil of the experimental field was loamy sand in texture, low in organic carbon (0.18 %) and available nitrogen (171 kg/ha), medium in available P2O5 (37.2 kg/ha) and low in available sulphur (6.8 kg/ha) with soil pH of 7.3. Application of 75 kg N/ha along with 50 kg P2O5 /ha and 40 kg S/ha resulted in higher seed yield, oil and protein content, as well as net returns.